From Immigrant to Establishment: A Black Family’s Journey - Dawson, Hilary (Ontario History, 2007)
This is the remarkable story of a Black family who came to Toronto in the 1830s, escaping from bondage and racism in the United States. The Lafferty family achieved levels of education and professional prominence that could only be dreamed of by free Blacks south of the border. One of their sons in particular – Alfred Lafferty, born in Toronto in 1839 – would rise to the position of principal of several grammar schools in different parts of the province, and become the first Black lawyer in Chatham, Ontario. His personal history provides a fascinating illustration of race and class in nineteenth-century Ontario. It demonstrates one family’s accommodation to the restrictions imposed by Canada’s unspoken prejudice against people of colour.